Concepts, Structure and Developments of High-Reliability Cyber-Physical Fusion Based Coordinated Planning for Distribution System - Gao, Chong; Wang, Tianlin; Cao, Huazhen; Wang, Ziyao; Yu, Tao; Cheng, Ran (Frontiers in Energy Research, 2021)
Coordinated control is imperative for the distribution network with the integration of wind power, photovoltaic system, and energy storage system. Meanwhile, the advanced automation terminal, intelligent control technology, and information communication technologies have greatly promoted the informatization of distribution network which also increase the correlation between the physical system (primary system) and the cyber system (secondary system). Hence, it is critical to comprehensively coordinate the planning of the cyber-physical system for building a highly reliable power grid. This work summarizes a series of challenges brought by the highly coupled cyber-physical system, such as the primary and secondary collaborated planning models and solution algorithms. Then, the reliability assessment theories of cyber-physical system and their application in distribution network planning models are introduced. Finally, three development directions of distribution network planning in the future are proposed considering primary and secondary system coordinated planning.